ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA BATAM SELATAN - Junita, Melssyka; Husda, Anggun Permata (LPPM Universitas Putera Batam, 2023)
The author's research is to evaluate the compliance level of individual taxpayers in Batam City. by utilizing thevariable tax amnesty and tax socialization Using a quantitative approach, this research is indicated as a causalassociative research. This study aims to provide and understand the relationship between the variablesinvolved, as measured by a numerical scale. The data collection method uses a questionnaire and distributesit to all individual taxpayers and the number of samples in this study is 100 personal taxpayers registered atKPP Pratama South Batam. Statistical test results show that tax amnesty has a positive effect on taxpayercompliance and tax socialization has a positive effect on taxpayer compliance. Statistical test results show thattax amnesty and tax socialization produce an Fcount of 22.665 and a significance of 0.00. Therefore, the testresults show that tax amnesty and tax socialization have a simultaneous effect on individual taxpayercompliance